2019
DOI: 10.1530/rep-19-0233
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles secreted during blastulation show viability of bovine embryos

Abstract: Extracellular vesicles (EVs) secreted by blastocysts may be clinically relevant, as indicator of embryo viability on in vitro fertilization. We tested if the characteristics of EVs secreted during blastulation are related to embryo viability. Morulae were individually cultured in SOF media depleted of EVs until day 7.5 post IVF. Viable embryos were determined by a system of extended in vitro culture of bovine embryos until day 11 (post-hatching development). Afterward, a retrospective classification of blastoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 78 publications
4
37
0
Order By: Relevance
“…El Hajj et al [38] suggested that decreased SNORDs promoter region methylation in ICSI children may modulate cancer susceptibility, based on the identification of SNORDs such as SNORD11 as being differentially methylated in ICSI versus control umbilical cord blood samples, showing a relationship to processes during early embryonic development. Interestingly, several SNORDs have been identified in EVs secreted by embryos during in vitro culture [39]. From a total of 32 snoRNAs identified, two (SNORD110, SNORD81) were exclusively present in media from viable embryos, whereas media from non-viable embryos had three exclusive snoRNAs (SCARNA24, SNORD97, SNORD48), indicating them as potential biomarkers of embryo viability.…”
Section: Oviductal Evs Regulate Early Embryonic Development By Alterimentioning
confidence: 99%
“…El Hajj et al [38] suggested that decreased SNORDs promoter region methylation in ICSI children may modulate cancer susceptibility, based on the identification of SNORDs such as SNORD11 as being differentially methylated in ICSI versus control umbilical cord blood samples, showing a relationship to processes during early embryonic development. Interestingly, several SNORDs have been identified in EVs secreted by embryos during in vitro culture [39]. From a total of 32 snoRNAs identified, two (SNORD110, SNORD81) were exclusively present in media from viable embryos, whereas media from non-viable embryos had three exclusive snoRNAs (SCARNA24, SNORD97, SNORD48), indicating them as potential biomarkers of embryo viability.…”
Section: Oviductal Evs Regulate Early Embryonic Development By Alterimentioning
confidence: 99%
“…Preimplantation embryos from different species, including human, pig, mouse, and bovine, secrete EVs that can modify gene expression in maternal cells or in other embryos [8][9][10]. The characteristics of EVs, including their concentration, size, distribution, and content, might reflect embryo quality, thus making them potential markers of embryonic developmental competence [10][11][12][13]. In fact, the most competent bovine embryos secrete fewer but larger EVs during blastulation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of EVs, including their concentration, size, distribution, and content, might reflect embryo quality, thus making them potential markers of embryonic developmental competence [10][11][12][13]. In fact, the most competent bovine embryos secrete fewer but larger EVs during blastulation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the broad-spectrum possibilities for EVs application, EVs have been postulated as potential non-invasive biomarkers. For example, EVs can be used as a biomarker for embryo quality [90][91][92] to select good embryos before transferring them to female recipients or to know the receptivity/health of a uterus before performing an embryo transference [93]. In addition, the increasing knowledge about the role of EVs on reproductive events and ART efficiency will lead to the next challenge for the biology of reproduction field: the large-scale production of EVs to use them as additives to gametes and embryo culture media.…”
Section: Challenges For the New Era Of Art Developmentmentioning
confidence: 99%